EARLY ORAL RE-FEEDING ON ONCOLOGY PATIENTS SUBMITTED TO GASTRECTOMY FOR GASTRIC CANCER - Andressa Madalozo LAFFITTE; Camila Brandão POLAKOWSKI; Massakazu KATO (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2015)
Background: There is no advantage in maintaining patients on oral fasting after gastrointestinal elective resection. The early feeding up to 48 h can be beneficial, because it reduces infectious complications and hospital stay. Aim: Evaluate the evolution and tolerance of early oral diet in postoperative period after gastrectomy for gastric cancer. Methods: Anthropometric assessment was performed on the day of surgery, weight, height, body mass index and weight loss were measured. Acceptance of diet was evaluated as food intake (amount accepted) and gastrointestinal symptoms such as nausea, vomiting, constipation, diarrhea, abdominal distension, postoperative complications and hospital stay. Results: The sample consisted of 23 patients, 17 with partial gastrectomy and six with total gastrectomy. In the assessment of nutritional status 9% were malnourished, 54.5% normal weight, 9% overweight and 27.2% obese, but 54% had weight loss. There was good acceptance of the diet in 96,9% of the sample. Nausea and abdominal distension were present in 4,3% and 65.2% constipation. Surgical complications according to the Clavien scalle, 13% had grade V, 4.3% grade IIIA, 8.7% grade I and 73% did not have complications. The length of hospital stay was 5±2.2 days. Conclusion: Early postoperative re-feeding in total and partial gastrectomy was well tolerated by patients.